2017
DOI: 10.1590/0104-9224/si2201.08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Torch Weaving on the Microstructure, Tensile and Impact Resistances, and Fracture of the HAZ and Weld Bead by Robotic GMAW Process on ASTM A36 Steel

Abstract: Abstract:The effect of torch weaving on the microstructure, tensile strength, impact resistance and fracturing in robotic welded joints using varing welding speeds, voltages and currents was evaluated through fractography using scanning electron microscopy, tension, impact and micro-hardness tests and optic microscopy. Results indicated that linear, sinusoidal and circular weavings favored an increase of the width of the HAZ as well as a slight increase in yield resistance accompanied by hardening in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
(25 reference statements)
0
16
0
4
Order By: Relevance
“…The semi-automatic welded joints of ASTM A-633 (2013) HSLA steel obtained at a greater heat input and a higher wire feed rate exhibited lower Charpy impact energy in the reheated HAZ of the weld metal, as well as greater flat area of mixedfracture surfaces showing mainly brittle fracture in transgranular cleavage with bigger facets, containing well-defined river patterns and a reduction of small micro-hollows distributed throughout the surface (Mendoza et al, 2013;Guzmán et al, 2017). This impact fracture behavior was linked to the microstructural features of a fine network of fine acicular ferrite (Thewlis, 2004;Wan et al, 2010;Guzmán et al, 2017) surrounded by allotriomorphic ferrite, which changed in size and amount as a consequence of the increase in wire rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The semi-automatic welded joints of ASTM A-633 (2013) HSLA steel obtained at a greater heat input and a higher wire feed rate exhibited lower Charpy impact energy in the reheated HAZ of the weld metal, as well as greater flat area of mixedfracture surfaces showing mainly brittle fracture in transgranular cleavage with bigger facets, containing well-defined river patterns and a reduction of small micro-hollows distributed throughout the surface (Mendoza et al, 2013;Guzmán et al, 2017). This impact fracture behavior was linked to the microstructural features of a fine network of fine acicular ferrite (Thewlis, 2004;Wan et al, 2010;Guzmán et al, 2017) surrounded by allotriomorphic ferrite, which changed in size and amount as a consequence of the increase in wire rate.…”
Section: Resultsmentioning
confidence: 99%
“…The brilliance and granular appearance of the planar central zone, in differing sizes, could be associated with the fractographic features of the typical brittle fracture. From the observations made on the fractographs obtained by SEM from impact fractured surfaces, we observed that the fracture was mainly brittle with well-defined transgranular facets containing river patterns in the direction of propagation, as well as minimum ductile fracture representing by microvoid bands (Guzmán et al, 2017) within the surface and surrounding these facets. These fractographic features confirmed that the brittle fracture was made by cleavage.…”
Section: Experimental Fractographymentioning
confidence: 98%
See 3 more Smart Citations